2016
DOI: 10.1016/j.jhep.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in hepatitis C testing in U.S. veterans born 1945–1965

Abstract: Background/Aims Universal one-time antibody testing for hepatitis C virus (HCV) infection has been recommended by the Centers for Disease Control (CDC) and the United States Preventive Services Task Force (USPSTF) for Americans born 1945-1965 (birth cohort). Limited data exists addressing national HCV testing practices. We studied patterns and predictors of HCV testing across the U.S. within the birth cohort utilizing data from the national corporate data warehouse (CDW) of the U.S. Veterans Administration (VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…We found no disparities based on sex in the change in screening rates following the intervention, which is consistent with a previous study that found only slightly higher screening rates among female veterans than males (58.2 percent versus 54.5 percent). 11 However, another study found that male veterans were more likely than females to be tested for hepatitis C. 28 Both studies reported screening rates that were considerably higher than the national screening rates we found. These differences may be a result of the effective programs that the Department of Veterans Affairs has implemented to reduce barriers to implementation of the testing recommendation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We found no disparities based on sex in the change in screening rates following the intervention, which is consistent with a previous study that found only slightly higher screening rates among female veterans than males (58.2 percent versus 54.5 percent). 11 However, another study found that male veterans were more likely than females to be tested for hepatitis C. 28 Both studies reported screening rates that were considerably higher than the national screening rates we found. These differences may be a result of the effective programs that the Department of Veterans Affairs has implemented to reduce barriers to implementation of the testing recommendation.…”
Section: Discussionmentioning
confidence: 59%
“…29,30 Additionally, Sourik Sarkar and coauthors found significant regional variability in hepatitis C testing. 28 Taken together, these findings suggest the need for region-specific programs to augment guidelines to further improve screening.…”
Section: Discussionmentioning
confidence: 94%
“…Approximately half were HCV RNA positive, the majority of whom were referred to care . However, among 4,221,135 birth cohort veterans receiving care within the Veterans Administration health system between 2000 and 2013, significant variation in testing (7%‐83%) was observed, suggesting that implementation of birth cohort testing for HCV failed to be “universal” as initially planned . The model presented by Chhatwal et al further emphasizes the limitations of the birth cohort strategy, estimating that, under the current standard of care, 597,000 (95% confidence interval [CI], 542,000‐891,000) of an estimated 834,000 remaining viremic subjects (72%) will be unaware of their infection in 2020 in the United States …”
Section: Screening and Diagnosismentioning
confidence: 99%
“…Similarly, another study demonstrated increased HCV screening from 1.09 to 2.53 per 100,000 person‐years after release of US Preventive Service Task Force (USPSTF) guidelines, with the most dramatic increase occurring in the Northeast compared to other regions of the country . Despite these increases in HCV screening among baby boomer patients, disparities exist with some subgroups based on age, racial/ethnic minority status, gender, primary care visits, and comorbidities …”
mentioning
confidence: 99%